Operating conditions for current transformers in transition modes and their influence on relay protection; Интеллектуальные энергосистемы; Т. 3 - Pavlova A. V. (Научно-технический дискурс "Интеллектуальные энергосистемы", 2017)
Заглавие с титульного экрана